Heat Transfer Characteristics in Exhaust Port for Hydrogen Fueled Port Injection Engine A Transient Approach - M. M., Noor; M. M., Rahman; K., Kadirgama; R. A., Bakar; M. F. A., Rahim (2011)

(untitled)
This paper was investigated the transient heat transfer characteristics in exhaust port for hydrogen fueled port injection internal combustion engine (H2ICE). One dimensional gas dynamics was described the flow and heat transfer in the components of the engine model. The engine model is simulated with variable engine speed and air fuel ratio (AFR). Engine speed varied from 2000 rpm to 5000 rpm with increment equal to 1000 rpm and AFR was varies from stoichiometric to lean limit. The effects of AFR and engine speed on heat transfer characteristics for the exhaust port are also investigated. The baseline engine model is verified with previous published results. The obtained results clarify that transient heat transfer process inside exhaust port for port injection H2ICE were affected by the engine speed and AFR. It can be seen that for obtained results clarify that for transient analysis, the fluctuation with very small amplitudes for heat transfer coefficient and heat transfer rate during the compression, intake and part of power stroke. The rapid change for both of them occurs during the exhaust and part of power stroke due to the exhaust valve is open. The obtained results from the simulation can be employed to examine the emission production and engine performance.